Mesozoic-Tertiary tectonics of SE Ireland and genetic link to offshore extensional basins - Cunningham, Michael J. M. (Trinity College (Dublin, Ireland). Department of Geology, 2001)
This work shows that Mesozoic-Tertiary tectonics in Central-East and SE Ireland is more significant than previously recognised. A review of the existing geological and geophysical literature and structural mapping around the coastline of Dublin Bay identified important brittle shear zones. The lack of polygonisation and strained quartz grains in thin-section implies that these structures are post-Hercynian. The analysis of seismic, well logs, bathymetry and aeromagnetic data of the offshore Mesozoic Kish Bank basin showed that NNW-SSE compression and ENE-WSW extension was compatible with the geometry and kinematics of the youngest brittle structures that cut onshore outcrop at Sorrento Point (Co. Dublin). Regional correlation with both the Ulster and Lough Neagh-Larne basins showed that the most deformed structures (near Blackrock) were compatible with an Early Tertiary age whereas the younger structures are probably of Late Tertiary in age. The correlation was based on independent structural work on the Antrim basalts, and apatite fission track and vitrinite reflectance studies of the Irish Sea region, which indicates substantial post-Liassic erosion. Seismic evidence showed a previously unrecognised palaeo-channel flowing west from the Kish basin, possibly from the postulated Irish Sea dome. The channel comes onshore and corresponds with a topographic low.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin